Estudo de transição de fase no aminoácido L-Leucina por espectroscopia Raman - Nascimento, Adriane do (2016)
In this study, an investigation was conducted on the phase transition for the L-Leucine amino acids, as a function of temperature. The chosen method for this evaluation was the Raman Spectroscopy, which enable an accurate qualitative analysis for the vibrational modes of a composite. Additionally, the Differential Scanning Calorimetry (DSC) and X-Ray Diffraction (XRD) techniques were used, since it can provide, respectively, information regarding the physical and chemical properties of a composite for a given temperature and time, and characterization and identification of the crystalline structure composites. After the L-Leucine amino acid characterization at room temperature using Raman Spectroscopy, measures were taken at temperature intervals ranging from -60o C to 180o C, for both increase and decrease of temperature. Analyzing the data obtained from the Raman spectrum with temperature variation along with the thermographs and XRD patterns of the L-Leucine, modifications were observed on the Raman spectra of the CH, CH3, CO2- and NH3+ functional groups, with temperature intervals approximately the same as the ones observed in the phase shift, found in the thermographs and XRD patterns. This indicates that spectra modifications are related to the phase transitions in these functional groups. Therefore, the Raman Spectroscopy method in addition to enable the characterization and identification of the vibrational modes of the L-Leucine, was found effective for the identification of the phase transition by means of spectra analysis.